Moth plant Araujia sericifera, an exotic smothering vine in New Zealand: Surveys for candidate biocontrol agents in South America, agent prioritization and safety testing - Paynter, Quentin (2025)
Surveys in the native range of moth plant Araujia sericifera revealed a rich natural enemy biotaattacking the plant, including damaging primary pathogens and root-boring and seed-feedingarthropod guilds, contrasting with surveys in New Zealand (NZ) that found only generalistdefoliating and sucking arthropod herbivores and two mildly pathogenic fungi. A chrysomelidbeetle with root boring larvae Freudeita cupripennis, a fruit fly Anastrepha nigrotaenia, and adefoliating rust fungus Puccinia araujiae were prioritised as potential biocontrol agents. Hostrangetesting indicated that all three species are sufficiently host-specific to be released in NZ.Approval was obtained to release an Argentinian population of P. araujiae and F. cupripennis,collected in Uruguay. Importation of P. araujiae into NZ was deferred until issues associatedwith the implementation of the Convention on Biological Diversity and associated development of Access and Benefit Sharing legislation in Argentina were overcome. It is hopedthat this will proceed soon. Freudeita cupripennis was first released in 2019 and is establishedin NZ. An application to release A. nigrotaenia sourced from Uruguay was submitted in 2023.However, several other Anastrepha species are pests of fruit crops and some of NZ’s majorfresh produce trading partners require declarations stating Anastrepha spp. are absent from NZproduce. This has delayed approval for the release of A. nigrotaenia as exporters will no longerbe able to declare that the genus Anastrepha is absent from NZ if A. nigrotaenia is released tocontrol moth plant. Consequently, trade agreements will require amendments to accommodatethis.